2014
DOI: 10.1371/journal.pone.0088802
|View full text |Cite
|
Sign up to set email alerts
|

Functional Elastic Hydrogel as Recyclable Membrane for the Adsorption and Degradation of Methylene Blue

Abstract: Developing the application of high-strength hydrogels has gained much attention in the fields of medical, pharmacy, and pollutant removal due to their versatility and stimulus-responsive properties. In this presentation, a high-strength freestanding elastic hydrogel membrane was constructed by clay nanosheets, N, N-dimethylacrylamide and 2-acrylamide-2-methylpropanesulfonic acid for adsorption of methylene blue and heavy metal ions. The maximum values of elongation and Young’s modulus for 0.5% AMPSNa hydrogel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 33 publications
(29 reference statements)
1
14
0
Order By: Relevance
“…Comparing q exp (mg g −1 ) of the present system with the reported data for crosslinked Na‐AMPS polymers, it was found that the maximum adsorption capacity of the hydrogel towards MB was 434.8 mg g −1 . Moreover, it is found that the Na‐AMPS/SS‐Na cryogel and composite adsorb MB in a very short time and with higher dye adsorption capacities.…”
Section: Resultsmentioning
confidence: 57%
“…Comparing q exp (mg g −1 ) of the present system with the reported data for crosslinked Na‐AMPS polymers, it was found that the maximum adsorption capacity of the hydrogel towards MB was 434.8 mg g −1 . Moreover, it is found that the Na‐AMPS/SS‐Na cryogel and composite adsorb MB in a very short time and with higher dye adsorption capacities.…”
Section: Resultsmentioning
confidence: 57%
“…Meanwhile, their resistance to dissolution is mainly due to the formation of cross-links between network chains [17]. As an adsorbent, the contaminants were captured between fine pores of hydrogel developed via crosslinking networks; hence, adsorbed [18]. The high-water-content and porous structure networks help to diffuse the solute through PVA hydrogel structure to trap the contaminants from wastewaters.…”
Section: Introductionmentioning
confidence: 99%
“…Oil palm trees are agricultural plants and play an important role in the economic growth of Malaysia. OPB is biomass waste that is produced after palm oil is removed from the palm fruit for oil production [18,19]. It was found that the addition of OPB could greatly enhance the polymer hydrogel durability via increasing the fiber medium adherence into the hydrogel by granting an irregular surface.…”
Section: Introductionmentioning
confidence: 99%
“…NC gels are mostly prepared with nonionic monomers, such as AM or its derivative, but the formed materials generally have a relative narrow range of application Liu et al, 2006;Xiong et al, 2008). Laponite was first preadsorbed by nonionic monomers before further polymerization of ionic monomers, such as AA (Huang, 2012), SA (Hu et al, 2011), MAA (Hu et al, 2011), SMA (Hu et al, 2011(Hu et al, , 2009, or AMPS (Bao et al, 2014). To combat this problem, two main strategies were developed: (1) Laponite could be preadsorbed by nonionic monomers before further copolymerization of ionic monomers and (2) choosing specific ionic monomers to realize the homodispersion of Laponite.…”
Section: In Situ Polymerization Of Monomers In Dispersion Of Laponitementioning
confidence: 99%